48.8k views
5 votes
3y = -x+11

2x+4y= 14

Solve the system.

User Ali Gh
by
5.8k points

2 Answers

6 votes

Answer:

x = -1 and y = 4

Explanation:

Step 1: Solve 3y = -x + 11 for x

3y + x= -x + 11 + x

x + 3y = 11

x + 3y - 3y = 11 - 3y

x = −3y + 11

Step 2: Substitute -3y + 11 for x in 2x + 4y = 14

2(-3y + 11) + 4y = 14

Simplify both sides of the equation, and you get −2y + 22 = 14

−2y + 22 − 22 = 14 − 22

-2y = -8

-2y/-2 = -8/-2

y = 4

Step 3: Substitute 4 for y in x = −3y + 11

x = -3(4) + 11

Simplify both sides of the equation, and you get x = -1

User Poke
by
5.9k points
7 votes

Answer:

x = -1

y = 4

Explanation:

3y = -x + 11

2x + 4y = 14

Rearrange equation 1

It becomes

x + 3y = 11

2x + 4y = 14

Multiply equation 1 by 4 and equation 2 by 3

We have

4x + 12y = 44

6x + 12y = 42

Subtract equation 2 from one

We have

-2x = 2

Divide both sides by-2

x = -2/2

x = -1

Now substitute-1 for x in any of the equations to get y .

Using equation 1, we have

-1 + 3y = 11

Add 1 to both sides of the equation

-1 + 1 + 3y = 11 + 1

3y = 12

Divide both sides by 3

3y/3 = 12/3

y = 4

User The Anh Nguyen
by
6.1k points